Hybrid materials doped with lithium ions - Żelazowska, Elżbieta; Rysiakiewicz-Pasek, Ewa (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Sol–gel derived lithium-ion conducting organic–inorganic hybrid materials have been synthesized from tetraethyl orthosilicate (TEOS), propylene glycol, ethylene glycol dimethacrylate, poly(vinyl alcohol), vinyl acetate, ethyl acetoacetate, poly(methyl methacrylate), propylene carbonate and some other precursors and solvents. The mass fraction of the organic additions in the gels and the level of the lithium salt doping (LiClO4) were ~40 mass% and 0.01%, respectively. The morphological and structural properties of the gels were investigated by a scanning electron microscope equipped with energy dispersive X-ray spectroscopy (SEM/EDX), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR) and 29Si MAS Nuclear Magnetic Resonance (29Si MAS NMR). The hybrid gels obtained were amorphous and colourless transparent or slightly opalescent, with the room temperature ionic conductivities of the order of 10–3 Scm–1. The results of FTIR spectroscopy and 29Si MAS NMR investigations have revealed strong influence of the organic modification, resulting in the direct chemical bonding between organic and inorganic components of the gels. The WO3-based electrochromic cells with the hybrids obtained being applied as the electrolytes were able to be reversibly coloured and bleached in the optical transmittance range of ~58% to 5% at around 550 nm.
Optica Applicata, Vol. 40, 2010, nr 2, s. 383-396
Keywords: sol-gel; optyka; organic–inorganic hybrids; lithium electrolyte; ionic conductivity